1998
DOI: 10.1038/34193
|View full text |Cite|
|
Sign up to set email alerts
|

G-protein-coupled receptor of Kaposi's sarcoma-associated herpesvirus is a viral oncogene and angiogenesis activator

Abstract: The Kaposi's sarcoma-associated herpesvirus (KSHV/HHV8) is a gamma-2 herpesvirus that is implicated in the pathogenesis of Kaposi's sarcoma and of primary effusion B-cell lymphomas (PELs). KSHV infects malignant and progenitor cells of Kaposi's sarcoma and PEL, it encodes putative oncogenes and genes that may cause Kaposi's sarcoma pathogenesis by stimulating angiogenesis. The G-protein-coupled receptor encoded by an open reading frame (ORF 74) of KSHV is expressed in Kaposi's sarcoma lesions and in PEL and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
349
1
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 781 publications
(361 citation statements)
references
References 24 publications
8
349
1
3
Order By: Relevance
“…These proinflammatory mediators have been suggested to play a key role in the autocrine and paracrine maintenance of KS tumor. Several of these gene products have also been demonstrated to induce neoangiogenesis Arvanitakis et al, 1997;Boshoff et al, 1997;Bais et al, 1998). Thus, the control of latent to lytic replication in HHV-8-infected cells, and the expression of lytic gene products could play a key role in KS disease pathogenesis.…”
Section: Hhv-8 Latencymentioning
confidence: 99%
“…These proinflammatory mediators have been suggested to play a key role in the autocrine and paracrine maintenance of KS tumor. Several of these gene products have also been demonstrated to induce neoangiogenesis Arvanitakis et al, 1997;Boshoff et al, 1997;Bais et al, 1998). Thus, the control of latent to lytic replication in HHV-8-infected cells, and the expression of lytic gene products could play a key role in KS disease pathogenesis.…”
Section: Hhv-8 Latencymentioning
confidence: 99%
“…For example, it appears to couple to Gq in Cos-1 and HEK 293T cells, and activates the stress-activated kinases JNK and p38 in the later (Arvanitakis et al, 1997;Bais et al, 1998;Burger et al, 1999). In endothelial cells, vGPCR clearly signals via Gi and leads to increased cell survival (Couty et al, 2001;Montaner et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that KSHV vGPCR activates ERK-1/2 in COS-7, but not in HEK 293 cells (Bais et al, 1998;Sodhi et al, 2000), and we have recently shown constitutive activation of ERK-1/2 and p38 by vGPCR in PEL cells (Cannon et al, 2003). To determine which vGPCR downstream events required ERK-1/2 activation, BC3.14 cells were transfected with the indicated reporter constructs in Figure 3 and subjected to 50 mm PD98059, a specific inhibitor of ERK-1/2.…”
Section: Kshv Vgpcr Signals Via a Gi-pi3k/akt Axis To Activate Ap-1 Amentioning
confidence: 99%
“…In regard to this work, it is important to note that an association between HHV-8 and prostate cancer has not been established. The viral G protein-couple receptor (vGPCR) is a lytic protein that promotes cellular proliferation by simultaneously activating several signal transduction pathways, including MAPK, AKT and the transcription factor NF-κB (116)(117)(118). A second lytic protein, viral IL-6 (vIL-6) is a structural and functional homolog to cellular IL-6 (119) and through activation of the STAT3 pathway also contributes to cellular growth (120,121).…”
Section: Human Herpesvirus 8 (Hhv-8)mentioning
confidence: 99%